Accelerated iTBS-Induced changes in resting-state functional connectivity correspond with cognitive improvement in amnestic MCI - Aghamoosa, Stephanie; Nolin, Sara A.; Chen, Andrew A.; Caulfield, Kevin A.; Lopez, James; Rbeiz, Katrina; Fleischmann, Holly H.; Horn, Olivia; Madden, Katrina; Antonucci, Michael; Revuelta, Gonzalo; McTeague, Lisa M.; et al. (Brain stimulation, 2025)
Published results of our Phase I safety and feasibility trial of accelerated intermittent theta burst stimulation (a-iTBS) in mild cognitive impairment (MCI) due to Alzheimer's disease showed a large effect-size improvement in cognition. Further demonstrate target engagement by identifying whether changes in local and network-level functional connectivity relate to the observed cognitive improvement. Eighteen patients with MCI received 3-day a-iTBS (8 sessions/day) to the left dorsolateral prefrontal cortex at Beam F3 (14,400 total pulses) and completed MRI and cognitive testing at pre- and post-treatment. Based on electric field models, we selected 3 stimulated target regions of interest (ROIs) which belonged to the frontoparietal (FPN), default mode (DMN), and ventral attention (VAT) networks (3 target networks). Metrics of resting-state functional connectivity were computed at the ROI level (within-network degree: number of connections) and network level (segregation: strength of connectivity within-network relative to other networks). We correlated changes in cognition and connectivity of the target ROIs and networks; off-target ROI (primary visual) and networks served as negative controls. Improvements in cognition were associated with connectivity changes in the target ROIs and networks, but not in off-target negative controls. Positive associations were observed for degree of the l-DMN and segregation of target networks overall, with significant effects for DMN and VAT. Cognitive improvement following a-iTBS in MCI may be attributable to local and network-level reconfigurations in functional connectivity. These findings will inform larger trials designed to further evaluate the neural mechanisms of a-iTBS for cognition in MCI. •We conducted an open-label Phase I trial of accelerated iTBS.•We found target engagement in patients with MCI due to AD.•Changes in functional connectivity related to cognitive improvement.•These effects were observed for connectivity at both the local and network level.